2018
DOI: 10.3389/fmed.2018.00265
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Bacteremia Caused by Hypermucousviscous KPC-2 Producing Extensively Drug-Resistant K64-ST11 Klebsiella pneumoniae in Brazil

Abstract: We report a fatal bacteremia caused by Klebsiella pneumoniae in a 60–70-year-old patient from Brazil. The genomic analysis of three isolates (from blood culture, nasal and anal swabs) showed that the bacteremia was caused by a KPC-2 producing extensively drug-resistant K64-ST11 hypermucousviscous K. pneumoniae (hmKP) harboring several virulence and antimicrobial resistance genes. Although the isolates did not present virulence markers associated with hypervirulent K. pneumoniae (hvKP), they showed invasion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…pneumoniae presented higher virulence than CC11/258 isolates in the Galleria mellonella pathogenicity model ( Andrey et al, 2019 ). Although we had the limitation of not performing any pathogenicity animal model, in our study, the isolates of outbreak A (ST11/KPC-2) presented a higher average number of virulence genes when compared with the isolates from the other outbreaks (outbreak A: average = 35, range = 27–36; outbreak D: average = 20, range = 20–20; outbreak C: average = 19, range = 19–19; outbreak B: average = 6, range = 6–6), a fact that may enable ST11/KPC-2 isolates to be responsible for a high rate of invasive infections, as observed here and worldwide ( Lee et al, 2016 ; de Campos et al, 2018 ). The colibactin cluster genes were only observed in outbreak A, being present in all the isolates of this group, but were disrupted in 17.0%.…”
Section: Resultssupporting
confidence: 55%
“…pneumoniae presented higher virulence than CC11/258 isolates in the Galleria mellonella pathogenicity model ( Andrey et al, 2019 ). Although we had the limitation of not performing any pathogenicity animal model, in our study, the isolates of outbreak A (ST11/KPC-2) presented a higher average number of virulence genes when compared with the isolates from the other outbreaks (outbreak A: average = 35, range = 27–36; outbreak D: average = 20, range = 20–20; outbreak C: average = 19, range = 19–19; outbreak B: average = 6, range = 6–6), a fact that may enable ST11/KPC-2 isolates to be responsible for a high rate of invasive infections, as observed here and worldwide ( Lee et al, 2016 ; de Campos et al, 2018 ). The colibactin cluster genes were only observed in outbreak A, being present in all the isolates of this group, but were disrupted in 17.0%.…”
Section: Resultssupporting
confidence: 55%
“…However, a subsequent retrospective multicenter study showed that ST11-K64 must have been spreading in China for several years and represents the most common type of CR-hvKP ( Zhang et al, 2020 ). Indeed, de Campos et al (2018) reported a hypermucoviscous CRKP strain that caused a fatal bacteremia in a patient in Brazil in 2018. Our report of an interhospital outbreak of ST11-K64 provided further evidence that ST11-K64 K. pneumoniae may be a competent host strain for a hypervirulent plasmid, leading to CR-hvKP, and control measures should be urgently implemented.…”
Section: Discussionmentioning
confidence: 99%
“…K64 has emerged in a large-scale study in China. 41 We screened several virulence-associated genes through PCR. Both ST11 CRKP95 and ST1764 hvKP were positive for rmpA, rmpA2, and iroN genes, whereas ST11 CRKP95 was non-hypervirulent KP (non-hvKP) (negative for the string test).…”
mentioning
confidence: 99%